Reasons for (not) discontinuing antipsychotics in dementia. Issue 1 (26th July 2017) - Janus, Sarah I.M.; van Manen, Jeannette G.; Zuidema, Sytse U.; Snijder, Carina; Drossaert, Constance H.C.; Ijzerman, Maarten J.
Abstract : Background: The gap between high antipsychotic prescription rates for patients with dementia and the guidelines' advice to prescribe cautiously indicates that barriers to discontinuation exist. This exploratory study used the theory of planned behaviour to give a first overview of the factors that influence physicians to discontinue antipsychotics in nursing home patients with dementia. Methods: Forty‐one physicians in the Netherlands completed an online survey based on the theory of planned behaviour. Results: Half of the respondents agreed that antipsychotics have positive consequences for patients, such as calming effects. Physicians who indicated that they tend not to discontinue antipsychotics believe that antipsychotics are associated with positive consequences for nursing home staff. Physicians who tend to discontinue antipsychotics had a higher perceived behavioural control than those who indicated having a low intention. Conclusion: To enhance discontinuation of antipsychotics, interventions should focus on both patient‐related factors and staff‐related factors. Prescribing decisions are influenced by staff‐related factors that need to be addressed as well.